Platinum Nanoparticles Supported on Activated Carbon Catalysts for the Gas- phase Hydrodechlorination of Dichloromethane: Influence of Catalyst Composition and Operating Conditions - María Ariadna Álvarez-Montero; Juan Jose Rodriguez; Luisa María Gómez-Sainero (Nanomaterials and Nanotechnology, 2016)
DCM is classified among the most hazardous atmospheric pollutants and therefore, the development of safe methods for the disposal of residual DCM is of great importance. Activated carbon- supported catalysts containing platinum nanoparticles as the active phase, with a high proportion of metal in the zero-valent state, were prepared in order to obtain catalysts of high performance in the gas-phase hydrodechlorination (HDC) of dichloromethane (DCM). Catalysts with Pt particles of sizes as low as 1.6 nm per average metal particle were obtained, leading to a high effectiveness in the dechlorination of effluent. All catalysts showed high initial dechlorination activity; however, a lower surface acidity in the support led to a higher stability of the conversion during the operation, as it avoids coke formation. When increasing metal load up to 2% (w/w), platinum nanoparticles of similar sizes originated, while a greater amount of Pt0 was obtained; this process therefore improved dechlorination activity to a significant extent. DCM conversion up to 90% and selectivity for non- chlorinated products higher than 90% were achieved. The influence of DCM concentration in the feed and the H2/DCM molar ratio was also investigated.